Vertical Deflection from Dip Observation - Sinzi, A. M.; Owaki, N.; Suzuki, H. (The International Hydrographic Review, 2015)
Needless to say, knowledge about vertical deflection is indispensable to research in geodesy and geology. Around a small island, for example a volcanic islet, we may expect a certain amount of vertical deflection due to the attraction of the island and its subterranean magma mass. For this reason, particular consideration should be given to vertical deflection on the islands of and around Japan on account of their geological characteristics (fig. 1). These islands contain a number of volcanoes and they are situated at the edge of the Eurasian Continent which in the Northern Pacific Ocean is fringed by deep trenches. In order to determine the deflection in islands, Gougenheim (1959) tried applying data on the dip of the horizon, and this was followed by a discussion by Bhattacharji (1961). Far from an island, the general geoid can be approximated as a part of a spherical surface; it is at this surface that we aim for observations referred to the horizon. On the other hand, near the island the geoid is distorted, generally upwards, due to subterranean structure; the vertical at a station on the island is the normal to this distorted geoid. Then, the dip at the station in the line determined by the observation station and the centre of the island, and the dip in a perpendicular direction should differ by the amount of the vertical deflection at the station. It should be emphasized that the deflection so obtained is that relative to the general geoid, not to a reference ellipsoid as defined in the usual sense in geodesy. The present paper gives the results of work carried out to investigate the distribution of vertical deflection in some of the southern islands of Japan (Izu Syoto).